2018
DOI: 10.1038/s41598-018-28972-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of hydroclimatic teleconnection and a time-varying model for long-lead prediction of Indian summer monsoon rainfall

Abstract: Several cases of failure in the prediction of Indian Summer Monsoon Rainfall (ISMR) are the major concern for long-lead prediction. We propose that this is due to the temporal evolution of association/linkage (inherent concept of temporal networks) with various factors and climatic indices across the globe, such as El Niño-Southern Oscillation (ENSO), Equatorial Indian Ocean Oscillation (EQUINOO), Atlantic Multidecadal Oscillation (AMO), North Atlantic Oscillation (NAO), Pacific Decadal Oscillation (PDO) etc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 44 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…The threshold of the EED is 3.84 (at a 5% significance level with 1 degree of freedom), so the edges for which the EED < 3.84 are to be excluded. To F I G U R E 5 (a) 1-6 months lagged global fields of the sea surface temperature (SST) anomaly difference obtained by subtracting the mean global field associated with above-normal rainfall events from the mean global field associated with below-normal rainfall events in December over east Japan; (b) same as for (a), but in January over east Japan; and (c) same as for (a), but in February over east Japan check the acceptability of the obtained graph structure at a particular confidence level, a test statistic, known as the deviance, can be used (Dutta and Maity, 2018).…”
Section: Gm-copula Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The threshold of the EED is 3.84 (at a 5% significance level with 1 degree of freedom), so the edges for which the EED < 3.84 are to be excluded. To F I G U R E 5 (a) 1-6 months lagged global fields of the sea surface temperature (SST) anomaly difference obtained by subtracting the mean global field associated with above-normal rainfall events from the mean global field associated with below-normal rainfall events in December over east Japan; (b) same as for (a), but in January over east Japan; and (c) same as for (a), but in February over east Japan check the acceptability of the obtained graph structure at a particular confidence level, a test statistic, known as the deviance, can be used (Dutta and Maity, 2018).…”
Section: Gm-copula Approachmentioning
confidence: 99%
“…The prediction model is developed using C-Vine copula approach, in which a sequence of trees is identified to develop the conditional distribution of the target variable given the parents (Xiao, 2011;Bauer et al, 2012;Liu et al, 2015;Righi et al, 2015;Dalla Valle et al, 2016). The selection of each tree is based on a maximum spanning tree algorithm, where edge weights are chosen to reflect the dependencies and the final tree can be used for the prediction of the target variable given the input variables (Dutta and Maity, 2018).…”
Section: Gm-copula Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Srivastava, Pradhan, Goswami, and Rao () in noting the changing relationships between major modes of climate variability and the IM, point to the shift in the tropical climate in the late 1970s, especially the warming of the central Pacific and the Indian Ocean (IO), as the driver of this nonstationarity. Although not focusing of intraseasonal to interannual river flow forecasting, the work of Dutta and Maity () bears implications for attempts to develop river flow prediction models for the IM region using teleconnection indices such as ENSO as the predictors. They found that a statistical time‐varying prediction model for IM rainfall, which accounted for nonstationarity in ENSO/IOD/IM associations, to be superior in performance compared with a time‐invariant model that assumed stationarity.…”
Section: Modes Of Climate Variability and River Flowmentioning
confidence: 99%
“…Another important aspect is that the summer monsoon rainfall at regional scale over the Indian domain responds to the above‐mentioned large‐scale climatic indices in complex ways. Dutta and Maity (2018) studied the time‐varying association among two large‐scale climatic indices and ISMR and concluded the need to carry out a detailed analysis at finer spatial scale with a larger pool of large‐scale climatic indices. Several other studies have been performed on Indian rainfall; however, it is difficult to treat India as a single unit for interpreting the association with the large‐scale indices, as the association have seasonal and regional differences (Maity and Nagesh, 2006; Vathsala and Koolagudi, 2017).…”
Section: Introductionmentioning
confidence: 99%